2021
DOI: 10.37213/cjal.2021.31313
|View full text |Cite
|
Sign up to set email alerts
|

Does Prewriting Planning Positively Impact English L2 Students’ Integrated Writing Performance?

Abstract: This study compared English L2 writers’ (N = 111) performance on an integrated writing task from the Canadian Academic English Language (CAEL) Assessment under three prewriting planning conditions: required self-timed planning required fixed time planning, and suggested (i.e., optional) planning. The participants’ integrated essays were scored according to the CAEL writing bands by raters at Paragon Testing Inc. The effect of planning condition on the participants' planning time, writing time, and integrated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
1
2
2
Order By: Relevance
“…However, if test takers' cognitive processes rather than their writing performance are investigated while they complete independent and integrated tasks, differences may be found as it was the case regarding the raters' cognitive processes while they rated these two types of writing tasks in this study. Moreover, the results of this study were in contrast to Michel et al (2020) and Uludag et al (2021) who found that integrated writing tasks are more challenging for test takers and elicit more dynamic and varied behaviors and cognitive processes in test takers. This contradiction might be due to the nature of the participants in Michel et al's and Uludag et al's studies who were test takers versus the participants in this study who were raters.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, if test takers' cognitive processes rather than their writing performance are investigated while they complete independent and integrated tasks, differences may be found as it was the case regarding the raters' cognitive processes while they rated these two types of writing tasks in this study. Moreover, the results of this study were in contrast to Michel et al (2020) and Uludag et al (2021) who found that integrated writing tasks are more challenging for test takers and elicit more dynamic and varied behaviors and cognitive processes in test takers. This contradiction might be due to the nature of the participants in Michel et al's and Uludag et al's studies who were test takers versus the participants in this study who were raters.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings on the first research question corroborated some previous studies (Allen, 2004;Wolfersberger, 2007) but partially contradicted several others (Ahmadi & Mansoordehghan, 2015;Michel et al, 2020;Plakans, 2010;Uludag et al, 2021). The results of the first research question did not match those of Ahmadi and Mansoordehghan (2015) since in contrast to this study, they found that task type (independent vs. integrated) did not have a significant effect on the students' writing performance.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…De nos jours, les liens entre la lecture et l'écriture (ou encore entre l'oral, la lecture et l'écriture) sont bien connus des universitaires ou des apprenants de langue pour des objectifs spécifiques telles les études universitaires dans une langue additionnelle (Hirvela et Belcher, 2016;Zhao et Hirvela, 2015). La relation symbiotique entre la lecture et l'écriture est, jusqu'à présent, principalement explorée à des fins d'évaluation de compétence langagière ou pour soutenir l'intégration académique de ces apprenants (English for Academic Purposes) (Plakans, 2010(Plakans, , 2015Plakans et Gebril, 2017;Uludag et al, 2021). Les tâches ou les tests utilisés dans ces deux domaines sont connus sous différentes appellations, notamment integrated reading-writing task, reading-to-write task, integrated writing tasks.…”
Section: Les Tâches De Rédaction Intégrées En Contextes Universitairesunclassified
“…Jusqu'à présent, les chercheurs s'intéressant aux tâches intégrées ont travaillé avec des apprenants de la langue de l'université (souvent, des étudiants non anglophones qui étudient ou veulent étudier dans des universités ayant l'anglais comme langue d'usage) (Li et Flowerdew, 2020;Uludag et al, 2021). Pourtant, ce profil ne tient pas compte des expériences variées des personnes qui n'ont pas l'anglais comme langue première mais qui développent une littératie académique nécessitant l'anglais.…”
Section: Les Tâches Intégrées Plurilingues (Tip)unclassified